Cancer patients participating in a lifestyle intervention during chemotherapy greatly over-report their physical activity level: a validation study. Issue 1 (December 2016) - Vassbakk-Brovold, Karianne; Kersten, Christian; Fegran, Liv; Mjåland, Odd; Mjåland, Svein; Seiler, Stephen; Berntsen, Sveinung
Abstract Background The short form of the International Physical Activity Questionnaire (IPAQ-sf) is a validated questionnaire used to assess physical activity (PA) in healthy adults and commonly used in both apparently healthy adults and cancer patients. However, the IPAQ-sf has not been previously validated in cancer patients undergoing oncologic treatment. The objective of the present study was to compare IPAQ-sf with objective measures of physical activity (PA) in cancer patients undergoing chemotherapy. Methods The present study was part of a 12-month prospective individualized lifestyle intervention focusing on diet, PA, stress management and smoking cessation in 100 cancer patients undergoing chemotherapy. During the first two months of the lifestyle intervention, participants were wearing an activity monitor (SenseWear™ Armband (SWA)) for five consecutive days while receiving chemotherapy before completing the IPAQ-sf. From SWA, Moderate-to-Vigorous intensity PA (MVPA) in bouts ≥10 min was compared with self-reported MVPA from the IPAQ-sf. Analyses both included and excluded walking in MVPA from the IPAQ-sf. Results were extrapolated to a wearing time of seven days. Results Sixty-six patients completed IPAQ-sf and wore the SWA over five days. Mean difference and limit of agreement between the IPAQ-sf and SWA including walking was 662 (±1719) min. wk−1 . When analyzing time spent in the different intensity levels separately, IPAQ-sf reported significantly higher levels of moderate (602 min. wk−1, p  = 0.001) and vigorous (60 min. wk−1, p  = 0.001) PA compared to SWA. Conclusions Cancer patients participating in a lifestyle intervention during chemotherapy reported 366 % higher MVPA level from the past seven days using IPAQ-sf compared to objective measures. The IPAQ-sf appears insufficient when assessing PA level in cancer patients undergoing oncologic treatment. Activity monitors or other objective tools should alternatively be considered, when assessing PA in this population.